Biotechnological Applications of Bacterial Endophytes - Mercado-Blanco, Jesus; J.J. Lugtenberg, Ben (Current Biotechnology, 2014)
This review starts with a brief introduction on bacterial endophytes. Only small fractions of rhizosphere and phyllosphere bacteria are able to live inside the plant. Endophytes are bacteria and fungi that can be detected at a particular moment within the tissues of apparently healthy plant hosts without producing symptoms in or on the plant. Possible traits required by these bacteria to enter the plant and live inside will be discussed. Furthermore, we will focus on possible biotechnological applications of bacterial endophytes and present case studies as examples. Endophytes can promote plant growth, for example by the production of hormones or by making nutrients (such as nitrogen, phosphate and ferric ions) available to the plant. Endophytes can also promote plant growth indirectly, for example by suppression of plant diseases, by inactivating environmental pollutants, and by alleviating stresses of the plant caused by excess of the hormone ethylene, by heavy metals, by draught and by salinated soil. Some endophytic bacteria can produce nanoparticles which have numerous applications. At the end of the review we will discuss aspects involved in the commercialization of microbes.
Keywords: stress tolerance